2020
DOI: 10.1590/1678-4324-2020180573
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Degradation of Textile dye Orange-122 Via Electrospray Mass Spectrometry

Abstract: This work reports the study of the potential application of Zn/TiO2 catalysts, obtained by the solgel method, in processes of environmental decontamination through the reactions of photodegradation of textile dye, followed by electrospray mass spectrometry. The catalysts synthesis was performed according to a 2² factorial design with repetition at the central point. The characterization techniques used were: N2 adsorption measurements (BET method), scanning electron microscopy with energy dispersive X-ray (MEV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 16 publications
0
4
0
1
Order By: Relevance
“…the process and finally they produce materials with a high content of mesoporous and a high surface area, which can be used for the adsorption of high molecular weight species, such as azo-dyes [22,[24][25][26][27].…”
Section: Graphical Abstractmentioning
confidence: 99%
“…the process and finally they produce materials with a high content of mesoporous and a high surface area, which can be used for the adsorption of high molecular weight species, such as azo-dyes [22,[24][25][26][27].…”
Section: Graphical Abstractmentioning
confidence: 99%
“…This showed that adsorbents had a high micropore structure. Besides, no hysteresis loop was observed in the adsorption-desorption of the adsorbents; this indicated that mesopores of adsorbents were at a quite low number or none [26]. Pore size distributions (PSDs) for adsorbents were calculated with the Barret-Joyner-Hallenda (BJH) method [49], using N 2 adsorption branches with results illustrated in Fig.…”
Section: Adsorbent Characterizationmentioning
confidence: 99%
“…In the A.C. (IV) diffractogram, for example, no phase other than quartz was detected, indicating that the unit cell of the crystal lattice of this material was composed basically of the elements silicon and oxygen in a hexagonal arrangement. This change most likely came from the chemical activation with phosphoric acid and heat treatment that this material was subjected to; in fact, the intention of activating an adsorbent is to change its structure to provide the formation of a porous surface with high adsorbent capacity; the fact that the base material was rich in silicon allowed all materials to show peaks related to the silicon oxide phases, a material that is highly known in the literature for being a material with a rich porous structure and high adsorptive capacity [26,44,63].…”
Section: Adsorbent Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Os efluentes aquosos contendo óleos acarretam problemas ambientais quando entram, sem tratamento, em contato com corpos hídricos, como por exemplo a formação de filmes na superfície da água, o que acarreta em um aumento da DQO e DBO daquele ambiente, pela diminuição das trocas gasosas entre o corpo d'agua e a atmosfera uma vez que a incidência de luz é diminuída, o que acarreta na eutrofização daquele corpo d'agua e consequentemente no desbalanceamento entre a fauna e a flora (Magalhães et al, 2013;Hoss et al, 2018). A partir disso, o tratamento correto de efluentes contaminados com óleos lubrificantes é necessário para garantir o cuidado com o meio ambiente, para isso são usualmente utilizados processos de adsorção/absorção com materiais adsorventes e filtrantes para a retirada desses compostos do meio aquoso, porém o elevado custo desses processos gera uma dificuldade em sua aplicação (Castro et al, 2019;Castro et al, 2020;Hoss et al, 2018).…”
Section: Introductionunclassified